2016
DOI: 10.1016/j.jag.2016.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Mexico City land subsidence in 2014–2015 with Sentinel-1 IW TOPS: Results using the Intermittent SBAS (ISBAS) technique

Abstract: Differential Interferometric Synthetic Aperture Radar (DInSAR) can be considered as an efficient and cost effective technique for monitoring land subsidence due to its large spatial coverage and high accuracy provided. The recent commissioning of the first Sentinel-1 satellite offers improved support to operational surveys using DInSAR due to regular observations from a wide-area product. In this paper we show the results of an intermittent small-baseline subset (ISBAS) time-series analysis of 18 Interferometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
89
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(100 citation statements)
references
References 31 publications
3
89
0
Order By: Relevance
“…deformation signal been present in the data a smoother more confident subsidence pattern would almost certainly have been observed, as was present in previous studies of spatially correlated motion using the technique (Bateson et al, 2015;Sowter et al, 2013;Sowter et al, 2016). and fig.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 79%
See 1 more Smart Citation
“…deformation signal been present in the data a smoother more confident subsidence pattern would almost certainly have been observed, as was present in previous studies of spatially correlated motion using the technique (Bateson et al, 2015;Sowter et al, 2013;Sowter et al, 2016). and fig.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 79%
“…Results have greatly increased the density of measurements over regions largely dominated by rural land cover, leading to a more consistent overall coverage and a more confident interpretation. It has been used to determine surface movements in various application areas including; coal extraction in the UK (Sowter et al, 2013, Novellino et al, 2014a, Bateson et al, 2015, landslips in Italy (Novellino et al, 2014b), elevation changes associated with blanket peat in Wales (Cigna et al, 2014) and groundwater abstraction in Mexico (Sowter et al, 2016).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Finally, Sentinel-1A ascending mode images acquired between October 2014 and May 2016 (Table 1) and made available via the Sentinel Scientific Data Hub [27] were processed using an improved version of the ISBAS technique [25][26]. To create the small baseline interferograms a threshold of one-year temporal baseline was used, while values of the perpendicular baseline were all below 200 m, hence complying with the common threshold used in SBAS processing.…”
Section: Monitoring Datamentioning
confidence: 99%
“…Furthermore, this issue is particularly challenging when using C-band SAR data. The novel Intermittent Small Baseline Subset (ISBAS) method [40], which is related to the SBAS technique described by [41], permits pixels of variable coherence to be considered alongside those with consistently high coherence [42][43][44]. Over a range of land covers, it has been demonstrated that the ISBAS method provides up to 26 times more coverage than SBAS [45].…”
Section: Introductionmentioning
confidence: 99%